Clinical Characteristics of 5 COVID-19 Cases With Non-respiratory Symptoms as the First Manifestation in Children - Cai, Xiaofang; Ma, Yaoling; Li, Songbo; Chen, Yan; Rong, Zhihui; Li, Wenbin (Frontiers in Pediatrics, 2020)
An outbreak of novel coronavirus disease 2019 (COVID-19) occurred in Wuhan, China, in December 2019, and then rapidly spread to more than 80 countries. However, detailed information on the characteristics of COVID-19 in children is still scarce. Five patients with non-respiratory symptoms as the first manifestation were hospitalized from the emergency department, and later confirmed to have COVID-19 between January 23 and February 20, 2020, in Wuhan Children’s Hospital. SARS-CoV-2 nucleic acid detection was positive for all the patients. Four of the patients were male and one was female, and their ages ranged from 2 months to 5.6 years. All lived in Wuhan. One patient had a clear history of exposure to SARS-CoV-2, one had a suspected history of exposure, and the others had no exposure history. For three of the five patients, the primary onset disease required an emergency operation or treatment, and included intussusception, acute suppurative appendicitis perforation with local peritonitis, and traumatic subdural hemorrhage with convulsion, while for the other two it was acute gastroenteritis (including one patient with hydronephrosis and a stone in his left kidney). During the course of the disease, four of the five patients had fever, whereas one case had no fever or cough. Two patients had leukopenia, and one also had lymphopenia. In the two cases of severe COVID-19, the levels of CRP, PCT, serum ferritin, IL-6, and IL-10 were significantly increased, whereas the numbers of CD3+, CD4+, CD8+ T lymphocytes and CD16 + CD56 natural killer cells were decreased. We also found impaired liver, kidney, and myocardial functions; the presence of hypoproteinemia, hyponatremia, and hypocalcemia; and, in one of the cases, abnormal coagulation function. Except for one patient who had rotavirus infection, all the patients tested negative for common pathogens, including the influenza virus, parainfluenza virus, respiratory syncytial virus, adenovirus, enterovirus, mycoplasma, Chlamydia, and Legionella. Chest CT images of all the patients showed patches or ground-glass opacities in the lung periphery or near the pleura, even large consolidation. This case series is the first report to describe the clinical features of COVID-19 with non-respiratory symptoms as the first manifestation in children.